INVENTORIES: FROM FETISH TO CREED. - Kracke, Edward A. (The Accounting Review, 1941)
To the student of history, there is hardly a more interesting phase for study than the transition from early days of fetish-worshipping to later years of creed-formulation; when mere blind belief, the sole support of fetish, gives way to reasoning, or at least attempts at reasoning which develop into creed, somewhat analogous, it is present transitional period in accounting thought, in which people are critically analyzing certain conventions which are at least suggestive of fetishes, in struggle to formulate a creed called "Accepted Principles?' And, as in history, transition takes time; ready-made decalogues are not the rule. The discussion has to do with one of the episodes in that transition the tentative pronouncement on inventories by the Research Department of the American Institute of Accountants, a document which is one of the steps in the story of creed-formulation in respect to inventories; and inventories constitute a subject which certainly has not been free of fetishes.